2009
DOI: 10.1200/jco.2008.16.0630
|View full text |Cite
|
Sign up to set email alerts
|

Overall Genomic Pattern Is a Predictor of Outcome in Neuroblastoma

Abstract: The analysis of the overall genomic pattern, which probably unravels particular genomic instability mechanisms rather than the analysis of individual markers, is essential to predict relapse in NB patients. It adds critical prognostic information to conventional markers and should be included in future treatment stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
323
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 305 publications
(357 citation statements)
references
References 39 publications
25
323
1
8
Order By: Relevance
“…About 76% of tumors of 4S patients have several numerical aberrations confirming previous reports. 21,[31][32][33][34] Although the mechanism responsible for high frequency of numerical CNAs in NBs is unknown, we argue that it may be due to a failure of chromosome segregation during mitosis process. 35 It is noteworthy that three of five patients having disease progression showed 11q loss and 17q gain, and we speculate that these mutations drive the deregulation of tumor suppressor genes located at 11q and/or oncogenes located at 17q regions and responsible for NB aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…About 76% of tumors of 4S patients have several numerical aberrations confirming previous reports. 21,[31][32][33][34] Although the mechanism responsible for high frequency of numerical CNAs in NBs is unknown, we argue that it may be due to a failure of chromosome segregation during mitosis process. 35 It is noteworthy that three of five patients having disease progression showed 11q loss and 17q gain, and we speculate that these mutations drive the deregulation of tumor suppressor genes located at 11q and/or oncogenes located at 17q regions and responsible for NB aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of MYCN (MNA) is associated with rapid tumor progression and advanced stage disease (1, 2). Segmental chromosomal alterations frequently occur in older children with stage IV tumors and are the strongest predictors of relapse, indicating a role in neuroblastoma pathogenicity (3,4). The most common alterations require DNA double-strand breaks (DSB) resulting in segmental deletions of 1p, 3p, 4p, or 11q and/or gain of 17q, 1q, and 2p regions (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing-based genomic profiling identified the most frequent alterations including MYCN (26.5%), ALK (17.8%), ATRX (6.5%), CDKN2A (4.8%) and RPTOR (4.8%) in 230 neuroblastoma patient samples [7]. Both ALK and MYCN genes are located in chromosome 2p, a chromosomal alteration identified as a statistically significant prognostic factor [8]. It has been shown that ALK and MYCN drive tumor malignancy cooperatively.…”
Section: Introductionmentioning
confidence: 99%